Optimizing Data-Based Decision Making: Development And Implementation Of Decision Support System In Langkat Regency Government - Jonhariono Sihotang; Paska Marto Hasugian (INFOKUM, 2024)
Effective decision-making in local government is essential to improve the quality of public services and policies. The Langkat Regency Government faces challenges in managing data efficiently due to the limited integrated information system. This study aims to develop and implement a Decision Support System (DSS) to support data-based decision-making in local government. Using a mixed-method approach, data were collected through observation, interviews, questionnaires, and document analysis from related agencies. The developed DSS prototype integrates cloud computing and artificial intelligence to accelerate data analysis and generate policy recommendations. The results showed that DSS increased data processing time efficiency and decision accuracy by 40%. However, challenges such as resistance to change and limited infrastructure are still obstacles. Therefore, a strategy to increase human resource capacity and digitalization policies is needed to ensure the sustainability of DSS.